Development of Male External Urethral Sphincter and Tissue-Resident Stem/Progenitor Cells in Rats - Zhou, Feng (Stem Cells Dev, 2020)
Stress urinary incontinence (SUI) after prostate surgery is primarily caused by urethral sphincter damage. There are few effective therapeutic approaches for male SUI due to both insufficient study of the structure of the external urethral sphincter (EUS) and incomplete understanding of the resident EUS stem/progenitor cells. The goals of this study were to localize and to determine the distribution of tissue-resident stem/progenitor cells in the male EUS throughout EUS development and to understand the anatomic temporal patterns of the EUS. Newborn Sprague Dawley rats were intraperitoneally injected with the thymidine analogue, 5-ethynyl-2-deoxyuridine (EdU), and the EUS was harvested at five time points (1, 2, 3, 4, and 8 weeks postinjection). The tissue was then processed for EdU staining and immunofluorescence staining for stem cell markers Ki67 and proliferating cell nuclear antigen. We counted the EdU+ label-retaining cells (LRCs) at each time point and colocalized with each stem cell marker, also we isolated and cultured the cells in vitro. The results revealed that the number of EdU+ LRCs in each EUS cross-section decreased over time and that the LRCs were located immediately under the basal membrane of laminin, densely adherent to the muscle fibers. In addition, the thickness of the striated muscle layer developed much faster than the smooth muscle layer during EUS development. By 4 weeks, the structure of the EUS layers was well differentiated. The EUS resident stem/progenitor cells were isolated with MACS(®) MicroBeads system, and myogenesis was confirmed. In this study, we defined both the time-course development of the EUS and the distribution of resident stem/progenitor cells. This information is crucial for forthcoming studies regarding male micturition and for development of novel therapeutic approaches for postoperative male SUI.